APPLICATION OF THE PROJECT BASED LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN CLASS IIB FRACTIONAL MATERIAL OF SD NEGERI 4 BANDA ACEH - Samsuri, Alya; Khansa, Salma (Teunuleh Publisher, 2022)
This study aims to describe student activities by applying the Project Based Learning learning model to improve student learning outcomes in class IIB fractional material SD Negeri 4 Banda Aceh. This type of research is Classroom Action Research (PTK) which aims to improve the quality of learning in the classroom. The subjects in this study amounted to 22 grade IIB students of SD Negeri 4 Banda Aceh City. Data collection techniques are carried out by observation and learning outcome tests. Based on the results of research in cycles I, II, and III obtained the following data: (1) the results of observations on student activities in learning observed for three cycles, increased each cycle, namely: student activity in cycle I reached 85.22%, cycle II reached 87.37%, and cycle III reached 93.45%. (2) the learning outcomes of students in fractional material have increased in cycle I of classical completeness criteria reaching 50% with an average value of 73.63, in cycle II classical completeness criteria of 81.81% with an average value of 85, while cycle III of classical completeness criteria 95.43% with an average value of 93.63. From the results of the study, it can be concluded that the application of the Project Based Learning learning model on fractional material can improve the learning outcomes of grade IIB students of SD Negeri 4 Banda Aceh.